The main stages in the development of the official administration in Hungary - Józsa, Zoltán (Zbornik radova Pravnog fakulteta u Novom Sadu, 2020)
After a brief outline of the past, the study focuses on the three main elements of public administration: the organization, the tasks and competences and the characteristics of the staff. Different but complementary research methods (historical, comparative and dogmatic) show the changes in the management and operation of official administration over historical periods. The formalized, subordinated public administration is increasingly replaced by a customer friendly, service-like administration. The corresponding organizational framework is the government window system, while the institutions the Act of General Administrative Procedures provide the opportunity to implement fast, cheap and efficient services. The commitment, skills, and professionalism of the public administration staff remain the most important factor for the realisation of a modern, service-oriented state. Changes in the nature of official administration is not straight-line, but the tendency is the strengthening of the help and service image.